Nutritional Knowledge, Physical Activity, and The Incidence of Chronic Energy Deficiency in Female Students - Erika, Iche Florence; Simanjuntak, Betty Yosephin; Jumiyati, Jumiyati (Jurnal Kesehatan, 2024)
Female students aged 18-20, categorized as late teens, often suffer from chronic energy deficiency (CED), as indicated by upper arm circumference measurements. This condition can lead to anemia, impaired organ development, stunted physical growth, and reduced work productivity. This study investigates the relationship between nutritional knowledge, physical activity, and the incidence of CED among students at the Nutrition Department, Politeknik Kesehatan Kemenkes Bengkulu. An observational cross-sectional study was conducted with 92 participants. Nutritional knowledge was assessed using a self-administered questionnaire (Ques CA), physical activity was measured with the Baecky Physical Activity Questionnaire (BPAQ), and CED was determined by measuring upper arm circumference. The chi-square test analysis revealed no significant relationship between nutritional knowledge and CED (p-value=0.868). However, a significant relationship was found between physical activity and CED (p-value=0.001). Despite having good nutritional knowledge, many adolescents still experience CED due to its lack of application in daily life. Efforts are needed to enhance attitudes and behaviors toward better knowledge application. Additionally, upper arm circumference measurements indicate that physical activity may influence subcutaneous fat mass.